L’icône et l’idole. Les représentations de Marie Stuart dans l’oeuvre de George Buchanan - Catellani-Dufrêne, Nathalie (Renaissance and Reformation / Renaissance et Réforme, 2013)
In 1561, George Buchanan definitely left France to live in Scotland where he became court poet of the Catholic Queen Mary Stewart, even if he publicly became Protestant. At the beginning, the humanist composed a few epigrams in which the queen is depicted as a good sovereign who restores the Golden Age in Scotland. A few years later, Buchanan depicted Mary Queen of Scots as a tyrant in his Rerum Scoticarum Historia, published in 1582. This article will provide a comparison between Buchanan’s different works (poetical works, tragedies and political and historical works) and show that the aesthetic choices and the references and quo- tations of ancient writers are based on Buchanan’s political thought about the Good King and the Tyrant, as we can read in the De jure regni apud Scotos dialogus, published in 1579.